التشريح العضلي لحركة اليد اليمنى في أداء بعض التقنيات العزفية على آلة التشيللو - يوسف، خالد محمد (جامعة حلوان - كلية التربية الموسيقية, 2018)
ليس هناك أدنى شك أن إلمام العازف بكيفية حركة القوس لأداء المصطلحات التعبيرية من الضروريات الهامة لارتباط تلك المصطلحات بالتقنيات العزفية المصاحبة للمقطوعات التي تتطلب من العازف معرفة دقيقة لظاهرة الصوت الناتج عن أي حركة يقوم بها على الآلة ويتوقف طبيعة هذا الصوت على كيفية هذه الحركة وكيفية فهم العزف لأداء العضلي لحركة اليد اليمنى المستخدمة في العزف على الآلة. وقد لاحظ الباحث وجود قصورا في اهتمام الدارسين وبعض العازفين لبعض التقنيات العزفية الخاصة بالقوس والتي تعد من الأهمية في إبراز المشاعر والانفعالات الإنسانية داخل العمل الموسيقي مما قد يحد من براعتهم ويؤدي إلى عدم مقدرتهم على إخراج العمل بالشكل اللائق - الأمر الذي دفع الباحث إلى إلقاء الضوء على العضلات المستخدمة أثناء حركة اليد اليمنى بالقوس من خلال بعض تقنيات العزف على الآلة. وانقسم البحث إلى جزئين: أولا: الإطار النظري: 1) ويشمل نبذة تاريخية عن قوس آلة التشيللو ونشأته وتطوره. 2) الجهاز الحركي في جسم الإنسان. 3) أنواع الانقباض العضلي. 4) الهيكل العظمي لجسم الإنسان. ثانيا: الإطار التطبيقي:- ويشمل 1) تفسير وتحليل تقنيات أداء القوس عينة البحث 2) نماذج العضلات العاملة لحركة اليد اليمنى المستخدمة في أداء ثم عرض النتائج وتفسيرها
There is no doubt that the knowledge of the player how to move the bow to the performance of the terms of expression is an important necessity to link those terms with the techniques associated with the pieces that require the player to know the precise sound phenomenon resulting from any movement on the machine depends on the nature of this voice on how this movement and how to understand the play For the muscular performance of the right hand movement used to play the machine. The researcher noted the lack of interest in the students and some of the instrumentalists of the arc, which is important in highlighting the emotions and emotions in the human music work, which may limit their proficiency and lead to their inability to produce the work properly - which prompted the researcher to shed light on The muscles used during the movement of the right hand in the arc through some techniques of playing the machine. The research was divided into two parts: First: The theoretical framework: 1) Includes a historical overview of the arc of the cello and its origin and development. 2) the motor system in the human body 3) I contract my muscles 4) The Great Structure of the Human Body Second: Application Framework: - Includes 1) Interpreting and analyzing arc performance techniques 2) Working muscle models of the right-hand movement used in performance Then view and interpret the results
Keywords: التلحين الموسيقي -- آلة التشيللو -- الآلات الوترية -- تقييم الأداء